Preferences for Explanation Generality Develop Early in Biology But Not Physics. Issue 4 (11th April 2017) - Johnston, Angie M.; Sheskin, Mark; Johnson, Samuel G. B.; Keil, Frank C.
Abstract : One of the core functions of explanation is to support prediction and generalization. However, some explanations license a broader range of predictions than others. For instance, an explanation about biology could be presented as applying to a specific case (e.g., "this bear") or more generally across "all animals." The current study investigated how 5‐ to 7‐year‐olds ( N  = 36), 11‐ to 13‐year‐olds ( N  = 34), and adults ( N  = 79) evaluate explanations at varying levels of generality in biology and physics. Findings revealed that even the youngest children preferred general explanations in biology. However, only older children and adults preferred explanation generality in physics. Findings are discussed in light of differences in our intuitions about biological and physical principles.